Ommochrome Wing Pigments in the Monarch Butterfly Danaus plexippus (Lepidoptera: Nymphalidae). Issue 6 (23rd December 2022) - Forman, Kyri A; Thulin, Craig D
Abstract: Monarch butterflies ( Danaus plexippus ) use bright orange coloration to warn off predators as well as for sexual selection. Surprisingly the underlying pigment compounds have not been previously characterized. We used LCMS and fragmentation MS (including MSMS and MS n ) of extracted pigments from nonmigratory summer-generation female monarch forewings to identify and provide relative quantitation of various orange pigments from D. plexippus . We observed seven ommochrome pigments, with xanthommatin and decarboxylated xanthommatin being the most abundant followed by xanthommatin methyl ester. Among the seven pigments, we also observed molecules that correspond to deaminated forms of these three amine-containing pigments. To the best of our knowledge, these deaminated compounds have not been previously discovered. A seventh pigment that we observed was α-hydroxyxanthommatin methyl ester, previously described in other nymphalid butterflies. We also show that chemical reduction of pigment extracts results in a change of their color from yellow to red, concomitant with the appearance of dihydro-xanthommatin and similarly reduced forms of the other pigment compounds. These findings indicate that monarchs may employ differences in the redox states of these pigments in order to achieve different hues of orange.